Chapter 7 A Performative Approach to Mixed Methods Research - Schoonenboom, Judith (Taylor & Francis, 2024)
This chapter explores the foundational idea of a performative approach: that our methods and concepts bring different research worlds into being. It has two different objectives. The first is to show that a performative approach can form the foundation for all research. Throughout this chapter, readers will recognize forms of data collection and data analysis that have been classified as postpositivist (questionnaires) or constructivist (interviews). A performative approach recognizes these different types of research yet views them all as acts that bring research worlds into being. The second objective is to show how a performative approach can form the foundation for mixed methods research. In contrast to a common view that integration in mixed methods research is about combining different realities into one coherent one, developing mixed methods theory in a performative approach is about integrating statements resulting from different worlds. These worlds themselves and their differences remain and are not resolved. Thus, in performative mixed methods research, deciding between two worlds that represent controversial statements, a common procedure in the sciences, hardly plays a role.